Are Voiding volumes and frequencies different in the three-day voiding diary in children with lower urinary tract dysfunction - ŞEKERCİ, ÇAĞRI AKIN; YÜCEL, SELÇUK; TARCAN, TUFAN (My University, 2023)
HYPOTHESIS / AIMS OF STUDYInitial evaluation of children presenting with lower urinary tract (LUT) symptoms includes physical examination, urinalysis, symptom scores, voiding diary (VD), uroflowmetry, and residual urine measurement. VD is an important tool that provides information about voiding volumes (VV), voiding frequency (VF) and habits, and it is recommended to be applied for at least 2 days in International Children Continence Society (ICCS) and European Urology Association (EAU) guidelines. However, some studies have reported similarities in VV between days at three-day VD. We hypothesized that the VV and VF between days may vary depending on the severity of the symptoms. Therefore, in this study, it was aimed to compare VV and VF values between days according to bladder capacity and symptom score.STUDY DESIGN, MATERIALS AND METHODSChildren who applied to the pediatric urology clinic due to LUT symptoms between 2022 and 2023 were included in the study. The records were evaluated retrospectively. Children with neurological deficits and missing data were excluded from the study. All children were evaluated in accordance with ICCS and EUA recommendations and underwent VD for 3 days. Mean VV and VF values of the whole group for each day were compared and subgroup analyzes were performed. The first subgroup was created according to Voiding Dysfunction Symptom Score (VDSS). VDSS by Akbal et al. was filled in by all parents. Children were divided into two groups as below and above the cut-off value of 8.5 showing LUT dysfunctions. The second subgroup was formed according to bladder capacity (BC). Bladder capacity is calculated as: uroflowmetry voided volume + residual urine volume. The Koff formula was used to calculate the expected bladder capacity (EBC) by age. BC/EBC of less than 65% was considered a low-capacity bladder (1). Decreased VF was accepted as <4 per day, normal VF 4-7 per day, and increased VF >7 per day.RESULTSA total of 109 (53 girls (48.6%), 56 boys (51.4%)) children with a median age of 8 (3-17) were included in the study. 77 (70.6%) children were diagnosed with overactive bladder, 8 (7.4%) with dysfunctional voiding, and 24 (22%) with monosymptomatic enuresis nocturne. The mean VVs between days were similar in the whole group (p=0.759) (Table 1). Moreover, the mean VV of the first day was similar to the average of both the first two days and the three days (p=0.021, p=0.490). Also, the maximum and minimum VVs were similar between days (1st day= 215.29+/-116.10 & 70.51+/-54.56 ml, 2nd day= 222.09+/-249.86 & 71.75+/-56.82 ml, 3rd day= 205.99+/-110.98 & 69.15+/-44.83 ml, p=0.942, p=0.160). In subgroup analyses based on gender, bladder capacity, and symptom score, mean VV was also found to be similar (Table 1). VF values were found to be significantly different between days. There was also a difference between VF values in children with VDSS>8.5 (p=0.012) and BC/EBC (%) >65 (p=0.030) (Table 2). In addition, 72 (66.1%) normal VF, 5 (4.6%) decreased VF, 32 (29.4%) increased VF were detected in first day; 75 (68.8%) normal VF, 10 (9.2%) decreased, 24 (22%) increased VF in second day; 77 (70.6%) normal VF, 6 (5.5%) decreased VF, 26 (23.9%) increased VF in third day.INTERPRETATION OF RESULTSVD is a highly useful tool that allows to show voiding habits, features of bladder function and is characterized by being an easy, non-invasive, no cost method. A properly completed VD provides information about VV, VF, presence and type of incontinence, enuresis, and fluid intake habits. Although at least two or three days of FVC is recommended, it is known that this form is difficult for parents to fill out, especially during school days. In the study of Franck et al., in which they evaluated the voiding diaries of 89 children, it was reported that the VF and mean VV were similar between the three days, but the maximum voiding volumes gradually decreased (2). The authors stated that one day\"s VD may be sufficient to evaluate LUT dysfunctions and shows good correlation with the three-day chart. Unlike these results, present study showed that VVs are similar in all group and sub-group analyses but there are differences between VFs. In another study, mean VV, maximum VV, and fluid intake were shown to be similar between 2- and 3-day VD (3). In addition, high number of voids numbers and low bladder capacities were found to be close to each other. It has been emphasized once again that a two-day VD may be sufficient for the evaluation of children with LUT dysfunctions. The highlight of the present study is the evaluation of VV and VF by forming subgroups according to symptom score and bladder volumes.CONCLUDING MESSAGEAlthough the voiding volumes of children with non-neurogenic LUT dysfunctions are similar between the days of the VD, there may be differences in the voiding frequencies particularly in children with IBSS>8.5 and normal bladder capacity. Therefore, we think that at least two daily voiding diary will contribute to strengthen the diagnosis and avoid over treatment.FIGURE 1Table 1. Comparison of voiding volume in frequency volume chartFIGURE 2Table 2. Comparison of voiding frequencies in frequency volume chartREFERENCESNevéus T, von Gontard A, Hoebeke P, Hjälmås K, Bauer S, Bower W, et al. The standardization of terminology of lower urinary tract function in children and adolescents: report from the Standardisation Committee of the International Children\"s Continence Society. J Urol. 2006;176(1):314-24.Franck HHM, Guedes ACS, Alvim YFS, de Andrade TMS, Oliveira LF, da Silva LI, et al. One-day voiding diary in the evaluation of Lower Urinary Tract Symptoms in children. Int Braz J Urol. 2023;49(1):89-96.Lopes I, Veiga ML, Braga AA, Brasil CA, Hoffmann A, Barroso U, Jr. A two-day bladder diary for children: Is it enough? J Pediatr Urol. 2015;11(6):348.e1-4.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Üroloji; Pediatrik Üroloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Urology; Pediatric Urology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; Cerrahi; Nefroloji; Surgery; Nephrology